Peran Guru Dalam Pengembangan Kurikulum Terhadap Kebutuhan Peserta Didik Di SMK Muhammadiyah 6 Karanganyar - Nurabidin, Usman; Luthfiah Nafi' Ramadhani; Fadiela Amara Husna; Dewi Tafaul Fatimah; Andriani; Praptiningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Curriculum development plays a crucial role in addressing contemporary educational challenges, particularly as students’ learning needs continue to diversify due to social transformation, technological advancement, and the evolving demands of the labor market. A responsive curriculum enables learning processes to be more contextual, flexible, and oriented toward the optimal development of students’ potential. This study aims to analyze the role of teachers in developing a curriculum that is responsive to students’ needs at SMK Muhammadiyah 6 Karanganyar. The main research question guiding this study is: how do teachers contribute to the development and implementation of a responsive curriculum that accommodates the diverse academic and non-academic needs of students? This research employs a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews with teachers, classroom observations, and document analysis related to curriculum planning and implementation. The collected data were analyzed using thematic analysis techniques involving data reduction, data display, and conclusion drawing to ensure validity and consistency. The findings indicate that teachers play a strategic role as curriculum developers by adapting learning materials, instructional strategies, and assessment methods to students’ characteristics and vocational competencies. Teachers are also actively involved in integrating character education, critical thinking skills, and industry-oriented competencies into the curriculum. This study contributes to the field of educational curriculum studies by emphasizing the importance of teacher involvement in creating a responsive curriculum, particularly in vocational education settings. The findings provide practical implications for schools and policymakers in strengthening teacher capacity to develop curricula that are adaptive to students’ needs and future workplace demands. sentences.